The Two Interpretations of the Poem of Rayhanat ar-Rooh on Morphology by Sharaf ad-Din al-Jandi: A Comparative Study - Hussein, Hameed Muslih; Aljubawi, Bayan Mohammed (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to provide a comparison between two interpretations of Rayhanat ar-Rooh on Morphology (Tasreef), a poem written by the poet Sheikh Sharaf ad-Din al-Jandi: an extended interpretation (al-Shareh al-Kabir) and another abbreviated one (al-Shareh as-Saghir). It also aims to argue for the precedence of the former over the latter. In addition, it also aims to prove that al-Kafiyyah fi al-Tasreef, a previously anonymous poem interpreted by as-Suyuti, is identical to Rayhanat ar-Rooh. Methods:The study uses the descriptive analytical approach. In the first section, it provides a short biographical account of Imam al-Jandi, especially because he is both the poet and author of the two interpretations. In the second, the study compares and contrasts the two interpretations. Results: The study proves that the poem that as-Suyuti interpreted is the same as the poem titled Rayhanat ar-Rooh and argues that its author is Sharaf ad-Din al-Jandi. This proof reinforces what the editor of Rayhanat ar-Rooh suggests, as the two interpretations confirm this attribution and both were written by the poet himself. It also proves that al-Shareh al-Kabir was composed before al-Shareh as-Saghir. Conclusions: This study introduces Imam al-Jandi, who wrote the poem Rayhanat ar-Rooh on Morphology and wrote its two interpretations al-Shareh al-Kabir and al-Shareh as-Saghir, and provides a detailed comparison between the two interpretations. It also shows the significance of Rayhanat ar-Rooh, which includes seven sections on morphology.